Estudo de parâmetros bioquímicos de cães relacionando com condição corporal, jejum e alimentação - Ferreira, Patricia Almeida (2012)
In this work we have studied the relationship between biochemical metabolic parameters (of dogs) and body score, fasting and feeding. In order to evaluate the glycemia values, using a digital (portable) glucometer, it was used 6μL of venous and capillary blood. On the other hand, when we evaluated the glycemia, through enzymatic method (laboratory), only venous blood was used. To analyze the metabolic curve we have collected blood samples of fasting dogs and 0:30, 1:30, 3:00, 6:00, 9:00, and 12:00 hours after feeding with premium industrial food. The laboratorial analysis were realized by enzymatic determination through colorimetry. In order to correlate the body scores and dogs morphometry, we have defined the body score, the body mass index (BMI), and the average values of cutaneous fat at the right rib cage, thoracic, and tail base regions. Also, we have measured the thoracic and inguinal circumference ratio. To compare the body scores with the metabolism of carbohydrates and lipids the dogs were classified, according to their weight, as ideal weighted, overweighted and obese. We have measured the glycemia, cholesterol (total and fractions), and triglycerides. The glycemia average values, obtained with the portable glucometer, of capillary and venous blood were similar. The glycemic, VLDL fraction, and triglyceride levels are changed after feeding, while the other analyzed parameters (total cholesterol, HDL and LDL fractions) are not. The obese dogs presented higher BMI and subcutaneous fat values and lower circumference ratio values, when compared with the ideal weighted and overweighted ones. The VLDL fraction and triglyceride values were higher when measured at the obese dogs. It is concluded that the portable glucometer is reliable, since the average values of venous and capillary glycemia are similars. At the experiment conditions, it is possible to perform the biochemical analysis of glycemia, total and fraction cholesterol, and triglycerides values after 3h fasting. The analysis of body mass index, together with the subcutaneous fat values and the circumference ratio has proven to be a fast and effective method to classify dogs as ideal weighted, overweighted and obese. At the studied conditions, obese dogs presented higher triglycerides and VLDL cholesterol fraction levels, when compared with overweighted dogs.